Development of iron-containing multiwalled carbon nanotubes for MR-guided laser-induced thermotherapy. (October 2011) - Ding, Xuanfeng; Singh, Ravi; Burke, Andrew; Hatcher, Heather; Olson, John; Kraft, Robert A; Schmid, Michael; Carroll, David; Bourland, J Daniel; Akman, Steven; Torti, Frank M; Torti, Suzy V
Aims: To test iron-containing multiwalled carbon nanotubes (MWCNTs) as bifunctional nanomaterials for imaging and thermal ablation of tumors.Materials & Methods: MWCNTs entrapping iron were synthesized by chemical vapor deposition. The T2-weighted contrast enhancement properties of MWCNTs containing increasing amounts of iron were determined in vitro . Suspensions of these particles were injected into tumor-bearing mice and tracked longitudinally over 7 days by MRI. Heat-generating abilities of these nanomaterials following exposure to near infrared (NIR) laser irradiation was determined in vitro and in vivo .Results: The magnetic resonance contrast properties of carbon nanotubes were directly related to their iron content. Iron-containing nanotubes were functional T2-weighted contrast agents in vitro and could be imaged in vivo long-term following injection. Iron content of nanotubes did not affect their ability to generate thermoablative temperatures following exposure to NIR and significant tumor regression was observed in mice treated with MWCNTs and NIR laser irradiation.Conclusion: These data demonstrate that iron-containing MWCNTs are functional T2-weighted contrast agents and efficient mediators of tumor-specific thermal ablation in vivo .